Heretical Sects': Mediation and Mediatization on New Media - Inayah, Sitti Syahar; Madani, Abubakar Idham; Bunyamin, Bunyamin; Amirullah, Amirullah (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
Efforts to spread deviant sects are now easier to reach all groups. This is due to the development of new media. Da'wah in new media can be done by anyone. One of the negative impacts of new media is the difficulty in distinguishing hoax information. In the context of spreading religious beliefs or beliefs that are considered heretical, now is the right moment. They can freely spread their ideas either with a clear identity or with a disguised identity. Communication media is used as a distribution channel as well as a tool for transformation. For this reason, this research aims to describe the mediation and mediatization of teachings or understandings that are considered heretical in new media, especially YouTube. This study used a qualitative approach with content analysis methods. The unit of analysis is a video shared by pilgrims Salamullah through the YouTube platform. Researchers perform mining data on the internet that has been available. The videos were analyzed using the multimodality method. The findings of this study are that there is a process of mediation and mediatization carried out by adherents of the Salamullah deviant sect. In the mediation process, the YouTube account is used as a channel to transmit ideas about their beliefs. As for mediation, it can be seen in the transformation of cognition in netizens. In addition, it was also found that in the user-generated media approach, cult followers become contributors or creators on their YouTube accounts. At the level of cognition, the changes in perception and negotiation of the meaning of heretical teachings can be formed. Indonesian culture which tends to accept new things will encourage adherents of heretical sects to use the media as a channel for conveying messages. It is this transformation that society and religious institutions must be aware of.